EVALUASI PENGGUNAAN KORTIKOSTEROID PADA PASIEN ANAK DI RSU PKU MUHAMMADIYAH YOGYAKARTA JANUARI - MARET 2015 - Bella Fevi Aristia; Woro Supadmi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Corticosteroids is widely used for inflammatory and autoimmune disorders. The aim of this research was to determine the prescription pattern of corticosteroids based on the type, route, body weight, diagnose, and evaluations appropriate of indications and dosage administration for pediatric patients at PKU Muhammadiyah Hospital in Yogyakarta city, Indonesia. This was a retrospective observational study with descriptively presented result. Pediatric patient medical record of who received corticosteroids in January-March 2015 was included to the study. The data collection included gender, age, body weight, diagnosis, type of corticosteroid, the manner and dosage. Evaluation of indications and dosage appropriateness were based on the Indonesian Ministry of Health Guideline for clinical practice, and other referral handbook. The results showed corticosteroids that widely used for outpatient were triamcinolone 77,91%, and dexamethasone injection 48,65% for outpatient. Route of administration for outpatient was 98,77% (oral) and 70,27% (parenteral) for inpatient. Corticosteroids were mostly used for acute bronchitis (42,24%) and asthma bronchitis (27,59%). The appropriate of administrations indication in outpatient was 90,06%, and inpatient was 89,66%. Dosage appropriate in outpatient was 100%, and inpatient was 48,65%. The type of corticosteroid for outpatient were triamcinolone, and inpatients were dexamethasone. The route of administrations corticosteroid were oral administrations for outpatient, and parenteral administrations for in patient. The diagnose in outpatients were acute bronchitis, and inpatient were asthma bronchitis. Indication and dosage appropriateness was higher in outpatient than those of in inpatient.